2016
DOI: 10.1021/acs.macromol.6b00432
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Crystalline Dendrimers Designed by Click Chemistry

Abstract: Liquid-crystalline dendrimers have been prepared from second-generation Percec-type poly(benzyl ether) dendrons or second-generation poly(aryl ester) dendrons carrying cyanobiphenyl mesogens. The Janus dendrimer, which combines the two types of dendromesogens, has also been synthesized. Those compounds have been prepared under copper-catalyzed azide−alkyne cycloaddition conditions. The mesomorphic properties have been studied by thermal analysis (POM, DSC) and small-angle X-ray scattering. Smectic A, nematic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…4) could also be used as a raw material for construction of triazole modules and then formation of dendrimer-like liquid crystal. 29 Various characterizations including a polarizing microscopy, etc., indicated that the dendritic polymer exhibited a columnar nematic liquid crystal structure. This nding thus opens up a new avenue to liquid crustal materials.…”
Section: Synthesis Based On the Reaction Between Poly-alkyne And Diazidementioning
confidence: 99%
“…4) could also be used as a raw material for construction of triazole modules and then formation of dendrimer-like liquid crystal. 29 Various characterizations including a polarizing microscopy, etc., indicated that the dendritic polymer exhibited a columnar nematic liquid crystal structure. This nding thus opens up a new avenue to liquid crustal materials.…”
Section: Synthesis Based On the Reaction Between Poly-alkyne And Diazidementioning
confidence: 99%
“…Among them, hyperbranched polymers have been well-studied in developing various nano/microscopic supramolecular structures, , but usually do not crystallize or assemble into ordered molecular solids due to their intrinsic structural irregularity and highly branched architectures. The incorporation of mesogenic units into hyperbranched polymer scaffold has demonstrated an ability to show liquid-crystalline (LC) mesomorphism. Most of hyperbranched LC polymers (HLCPs) can merely generate orientationally ordered nematic mesophase, while some higher ordered smectic, columnar, cubic, and even liquid quasi-crystalline structures that usually observed in their analogues of structurally perfect dendrimers remain a contemporary challenge. This underdeveloped situation in HLCPs largely limits the diversification in their structures and functions, whereas self-assembly of hyperbranched polymers can become more expected in this case where both three-dimensional dendritic architecture and facile one-pot synthesis are desired. , The shape-variable nature of the highly branched spheroidic morphology allows for various modes of packing, and the irregularity (or distribution) in structure and molecular weight provides additional possibilities to affect the crystalline process, , which would result in the observation of various phases. Thus, our intention here is to develop a well-organizable HLCP and to tune the optoelectronic property through control of the self-assembled hierarchical structures by regulation of the kinetics involved processing pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the trans state of the stilbene molecule is more stable than the cis state. 3 As shown in Figure 5, the UV–vis spectra of multiblock copolymers 2a – e were measured in THF solution. According to Figure 5, their most intense absorption bands were below 280 nm in the ultraviolet region, arising from the π–π* transition localized on the 2(5 H )-furanone ring within each polymer.…”
Section: Results and Discussionmentioning
confidence: 99%